PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA NEGERI 2 METRO - Gunawan, Ade (Bioedukasi Jurnal Pendidikan Biologi, 2012)
The research was to incrase of students critical thinking skills. The subject of this study were SMAN 2 Metro grade X4 class numbering 30 student in the second semester of the academic 2011/2012. And the object of his research is the critical thinking skills. The results showed that the implementation of problem-based learning model on Biology learning, can increase students critical thinking skills. Increase critical thinking skills is almost all indicators, such as the ability of clarification, argumentation skills, induction skills, deduction skills, and ability to perform and execute. Increase critical thinking skills that students can be seen from the increase in the average value of each point about the cycle I and cycle II. The success of critical thinking can also be seen from the increase in the thoroughness of learning, that is equal to 6 students in cycle I to cycle II is 24 students. The means the percentage of students who achieve greater value equal to 72 also increased, from 20% in cycle I to 80% in cycle II.Â Kata Kunci: Pembelajaran Berbasis Masalah, Keterampilan Berpikir Kritis